(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study is to analyze the human resource development model of sharia companies based on Islamic religious education for marketers, as well as the implementation of sharia company HR development models based on Islamic religious education for marketers at PT Asuransi Takaful Keluarga Jakarta. This study used qualitative research methods. Researchers chose to collect data by describing what the researchers encountered in the field. The data collection procedure used by the researcher in this research is observation, interview, and documentation. The results are HR development program at PT Asuransi Takaful Keluarga Jakarta, namely with two types, first, sharia training which is carried out every month and second, training for marketers is carried out with four levels of training, namely: fast start, basic training, intermediate training, and leader advance training. The new concept of sharia marketer education is not only a marketing competency that is considered, but also built and developed in aspects of Islamic religious education, namely monotheism and morals as exemplified by the Prophet Muhammad S.A.W. The implementation of the HR development model for sharia companies based on Islamic religious education for marketers at PT Asuransi Takaful Keluarga Jakarta is to make marketers more sincere, love customers (love customers), do not market by cheating, and feel that they are mujahid da'wah, and build mental awareness by soul marketing. After the marketing soul becomes the basis of the mindset of a marketer, the soul will become the basis of the company's movement and become the core of the implementation of the marketing strategy that will be carried out. If it has been implemented on an ongoing basis, then the concept of soul marketing can become a marketing morale for marketers. And this is the essence of Islamic religious education itself.